Granule powder and production method therefor

JP2025026434APending Publication Date: 2025-02-21TOSOH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024133823
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-08-09
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0009】 本開示により、顆粒化に供する原料粉末スラリーの有機成分の詳細な組成制御を必須とすることなく、プレス成形法によって、ハンドリング中の割れや欠けの発生が生じにくい強度を有する成形体が得られる顆粒粉末、及び、この様な顆粒粉末の簡便な製造方法の少なくともいずれかを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026434000001_ABST
    Figure 2025026434000001_ABST
Patent Text Reader

Abstract

To provide at least either of granule powder and its simple production method that can obtain a compact with high strength by a press molding method without the necessity of detailed composition control of an organic component of material powder slurry placed to granulation.SOLUTION: Ceramics granule powder contains ceramics powder and a binding agent, and also has absorption peak intensity of 0.023 count or more with a peak top at 1730±20 cm-1 in infrared spectrum per mass of the binding agent.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to ceramic granular powders and methods for producing the same. [Background technology]

[0002] Zirconia (zirconium dioxide, ZrO 2 Ceramics (sintered bodies) including ceramics such as sintered ceramics are produced by forming raw material powder into a compact (green compact) and sintering this (after calcining as necessary). Press molding, in which the raw material powder is filled into a die and pressed into shape, is commonly used to form the raw material powder. Normally, raw material powder has a small secondary particle size of 1 μm or less and low fluidity. For this reason, the raw material powder is granulated to produce granular powder with an aggregate size of several tens of μm (granulated powder), which is then used for press molding. In order to improve the fluidity as well as the properties of the raw material powder when it is molded, granular powder containing the raw material powder and organic components such as a binder is used.

[0003] For example, as a granular powder containing an organic component, for example, a granular powder obtained by spray-drying an organic component consisting of an acrylic copolymer resin, polyvinyl alcohol, polyalkylene oxide, and stearic acid and a ceramic powder is disclosed (Patent Document 1). Patent Document 1 discloses that such a granular powder can be used to obtain a molded body having excellent releasability during molding. Patent Document 2 discloses that a granular powder having a high average circularity can be obtained by controlling the bubble amount, viscosity, surface tension, etc. of the slurry. Patent Document 2 also discloses that the granular powder of Patent Document 2 is a raw material suitable for molding a laminate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2013 / 047413 [Patent Document 2] International Publication No. 2018 / 056331 Summary of the Invention [Problem to be solved by the invention]

[0005] It is disclosed that the granular powder of Patent Document 1 can obtain a molded body with high strength by increasing the molding pressure. However, for the granular powder of Patent Document 1, it is essential to use a raw powder slurry in which the composition of the organic components, including the binder, is controlled in detail. Furthermore, as a result of the inventor's investigation, it was confirmed that the molded body obtained from the granular powder of Patent Document 1 is prone to defects such as chipping of the ends during handling. On the other hand, Patent Document 2 discloses that the circularity of the granules can be controlled by adding an organic component to the raw powder slurry. In this way, the characteristics of the obtained granular powder were controlled by controlling the detailed composition of the organic components of the slurry of the raw powder to be granulated. It should be noted that Patent Document 2 suggests the use of a dispersant to control the circularity of the granular powder, but does not disclose any specific information about the dispersant and other conditions, and does not disclose any specific method for controlling the circularity.

[0006] The present disclosure aims to provide at least one of a granular powder that can be used to obtain a molded body having strength that is less likely to crack or chip during handling by a press molding method, without requiring detailed compositional control of the organic components of the raw material powder slurry to be subjected to granulation, and a simple method for producing such a granular powder. [Means for solving the problem]

[0007] Conventionally, granular powders suitable for moldability have been obtained by focusing on the composition of the slurry, such as the combination of raw material powders and organic components, or the raw material powders and organic components. In contrast, in the present disclosure, as an improvement in granular properties without detailed control of the slurry composition, the granulation conditions themselves have been studied. As a result, it has been found that by controlling the granulation conditions themselves, granular powders that give compacts with higher strength can be obtained, and thus defects are less likely to occur at the edges of the resulting compacts.

[0008] That is, the present invention is as defined in the claims, and the gist of the present disclosure is as follows. [1] Ceramic powder and binder, and the infrared spectrum of 1730 ± 20 cm per mass of the binder -1 The ceramic granule powder has an absorption peak intensity of 0.023 counts or more. [2] The granular powder according to [1] above, wherein the ceramic is zirconia. [3] The granular powder according to [2] above, wherein the zirconia is zirconia containing a stabilizing element. [4] The granular powder according to [3] above, wherein the stabilizing element is one or more selected from the group consisting of yttrium, magnesium, calcium, cerium and erbium. [5] The granular powder according to any one of [1] to [4] above, wherein the binder is at least one of a polyvinylpyrrolidone-based resin and an acrylic-based resin. [6] A granular powder according to any one of [1] to [5] above, wherein the binder content is 0.1% by mass or more and 8% by mass or less. [7] Lightly packed bulk density 1.10 g / cm 3 The granular powder according to any one of [1] to [6] above. [8] 15±0.5 g of the granular powder was filled into a cylindrical mold with a diameter of 25 mm and pressed at a pressure of 49 MPa. The measured density was 2.70 g / cm 3 The granular powder according to any one of [1] to [7] above. [9] A method for producing a granular powder according to any one of [1] to [8] above, comprising a step of spray-drying a slurry containing a ceramic powder, a binder and a solvent by setting the difference between the hot air temperature and the exhaust air temperature to 55°C or more.

[10] The manufacturing method described in [9] above, wherein the hot air temperature is 300°C or less.

[11] A method for producing a molded body using the granular powder described in any one of [1] to [8] above.

[12] A method for producing a calcined body using the molded body described in

[11] above.

[13] A method for producing a sintered body, using the molded body according to

[11] above or the calcined body according to

[12] above. Effect of the Invention

[0009] The present disclosure makes it possible to provide at least one of a granular powder that can be used to obtain a molded body having strength that is less likely to crack or chip during handling by a press molding method, without the need for detailed compositional control of the organic components of the raw material powder slurry to be subjected to granulation, and a simple method for producing such a granular powder. [Brief description of the drawings]

[0010] [Figure 1] SEM observation of granular powder of Example 2 (scale in the figure is 100 μm) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The granular powder of the present disclosure will be described with reference to an example of an embodiment. The configurations and parameters disclosed herein may be combined in any combination, and the upper and lower limits of the values ​​disclosed herein may be combined in any combination.

[0012] The "composition" is a substance having a certain composition, and examples thereof include one or more selected from the group consisting of powder, granules, a molded body, a calcined body, and a sintered body.

[0013] The term "powder" refers to a composition that is an aggregate of powder particles and has flowability. The term "zirconia powder" refers to a powder whose main component is zirconia, or a powder that essentially consists of zirconia.

[0014] "Granular powder" refers to a powder consisting of granular particles, and "granular particles" are particles (tertiary particles, granulated particles) formed by the slow aggregation of powder particles (particularly, at least one of primary particles and secondary particles) by physical force, and may contain organic components.

[0015] A "molded body" is a composition having a certain shape composed of powder particles aggregated by physical force, and in particular, a composition in a state in which no heat treatment has been performed after the shape has been imparted (e.g., after molding). A "zirconia molded body" is a molded body whose main component is zirconia, and is a molded body essentially made of zirconia. In this embodiment, the terms "molded body" and "compressed powder" are used interchangeably.

[0016] The term "calcined body" refers to a composition having a certain shape composed of fused particles, and is a composition in a state in which it has been heat-treated at a temperature lower than the sintering temperature. The term "zirconia calcined body" refers to a calcined body containing zirconia as the main component, and is a calcined body essentially consisting of zirconia.

[0017] The term "sintered body" refers to a composition having a certain shape composed of crystal grains, and is a composition in a state in which it has been heat-treated at a temperature equal to or higher than the sintering temperature. The shape of the sintered body of this embodiment may be at least one selected from the group consisting of spherical, approximately spherical, elliptical, disk-shaped, cylindrical, cubic, rectangular, polyhedral, and approximately polyhedral. Furthermore, any shape may be used to achieve a specific purpose, such as various applications. The term "zirconia sintered body" refers to a sintered body mainly composed of zirconia, and further, a sintered body essentially composed of zirconia.

[0018] The term "stabilizing element" refers to an element that has the function of stabilizing the crystal phase of zirconia by dissolving in zirconia.

[0019] The "BET specific surface area" is a value measured under the following conditions using the BET multipoint method (5 points) in accordance with JIS R 1626, with nitrogen as the adsorption gas.

[0020] Adsorption medium:N 2 Adsorption temperature: -196℃ Pretreatment conditions: Degassing in air at 250℃ for 1 hour or more The BET specific surface area can be measured using a common device (for example, Tristar II 3020, manufactured by Shimadzu Corporation).

[0021] The "average granule particle size" is the average particle size of granular powder measured by a dry method, and is the particle size (median size) corresponding to a volume fraction of 50% on the volume particle size distribution curve measured under the following conditions using a general particle size distribution meter (product name: MT3100II, manufactured by Microtrack-Bell). Measurement sample: Granular powder Refractive index of zirconia: 2.17 Refractive index of air: 1.333 Measurement time: 10 seconds

[0022] "Light bulk density" is the density measured by passing granular powder through a sieve with 500 μm openings and allowing it to fall freely from a height of 35 mm to a volume of 100 cm 3 Fill the container with granular powder and place it in a 100cm container. 3 The mass [g] of the container was measured using a balance, and the mass [g] of the filled granular powder was calculated by subtracting the mass [g] of the container. The volume [100 cm 3 ] per unit mass [g / cm 3 ] can be calculated as follows.

[0023] The term "powder X-ray diffraction pattern" refers to the XRD pattern of a composition obtained by powder X-ray diffraction (hereinafter also referred to as "XRD") measurement under the following conditions. Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 2° / min Measurement range: 2θ=26°~33° Acceleration voltage / current: 40kV / 40mA Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm

[0024] The XRD measurement can be performed using a general X-ray diffractometer (e.g., Ultima IV, manufactured by RIGAKU Corporation). When the composition is a calcined body or a sintered body, the surface is polished to a surface roughness Ra≦0.02 μm, and the XRD measurement can be performed on the surface.

[0025] Examples of XRD peaks corresponding to each crystal plane of zirconia measured in the above-mentioned XRD measurement include XRD peaks having peak tops at the following 2θ. XRD peak corresponding to monoclinic (111) plane: 2θ=31±0.5° XRD peak corresponding to monoclinic (11-1) plane: 2θ=28±0.5° XRD peak corresponding to tetragonal (111) plane: 2θ=30±0.5° XRD peak corresponding to cubic (111) plane: 2θ=30±0.5°

[0026] The XRD peak corresponding to the tetragonal (111) plane and the XRD peak corresponding to the cubic (111) plane are measured as a single overlapping peak. Therefore, I t (111)+I c (111) can be determined from the integrated intensity of one XRD peak having a peak top at 2θ=30±0.5°. The area intensity of each crystal plane can be obtained by profile fitting the XRD pattern after smoothing and background removal processing using a divided pseudo-Voigt function. Smoothing processing, background processing, and analysis of the XRD pattern such as calculation of area intensity can be performed using an analysis program attached to the X-ray diffraction device (for example, integrated powder X-ray analysis software PDXL Ver.2.2, manufactured by RIGAKU Corporation).

[0027] "Normal pressure sintering" is a method of sintering by heating the material to be sintered (such as a compact or calcined body) without applying an external force.

[0028] [Granular powder] This embodiment includes a ceramic powder and a binder, and has an infrared spectrum of 1730±20 cm per mass of the binder. -1 The ceramic granular powder has an absorption peak intensity of 0.023 counts or more, with a peak top at 1000 nm. By press-molding the granular powder satisfying this constitution, a molded body having a strength that is unlikely to crack or break (hereinafter also referred to as "chipping") during handling can be obtained.

[0029] The granular powder of this embodiment includes ceramic powder and is composed of granular particles including a binder and ceramic powder particles. The "ceramic powder" in the granular powder of this embodiment means the ceramic that is the main component (matrix), and further, the ceramic that is contained in the largest amount in the granular powder of this embodiment. The ceramic is preferably an oxide ceramic. The oxide ceramic, for example, alumina (Al 2 O 3 ), zirconia (ZrO 2 ), silica (SiO 2 ), Germania (GeO 2 At least one of alumina and zirconia is preferred, and zirconia is more preferred.

[0030] Hereinafter, the granular powder of this embodiment will be described taking as an example a case where the ceramic is zirconia (zirconia granular powder).

[0031] The zirconia contained in the granular powder of this embodiment is preferably zirconia containing a stabilizing element. The stabilizing element may be one or more selected from the group consisting of yttrium (Y), calcium (Ca), magnesium (Mg), scandium (Sc), cerium (Ce) and erbium (Er), and may further be one or more selected from the group consisting of yttrium, calcium, magnesium and cerium, or at least one of yttrium and cerium, and is preferably yttrium. The content of the stabilizing element may be an amount that stabilizes the crystal phase of zirconia in at least one of cubic and tetragonal, and is preferably an amount that stabilizes the crystal phase having tetragonal as the main phase. The content of the stabilizing element is preferably 1.5 mol% or more, 2.0 mol% or more, or 2.8 mol% or more, and 8.0 mol% or less, 6.0 mol% or less, or 4.2 mol% or less, and more preferably 1.5 mol% or more and 8.0 mol% or less, 2.0 mol% or more and 6.0 mol% or less, or 2.8 mol% or more and 4.2 mol% or less.

[0032] The content of the stabilizing element in this embodiment is the molar ratio (mol %) of the stabilizing element calculated as an oxide to the total of zirconia and the stabilizing element calculated as an oxide.

[0033] In addition to the zirconia powder, the granular powder of the present embodiment preferably contains one or more powders selected from the group consisting of alumina, silica, and germania (hereinafter also referred to as "additive components"), and more preferably contains alumina powder. The coexistence of zirconia and the additive components enables sintering of zirconia at a lower temperature. In this case, the content of the additive components is 0% by mass or more, more than 0% by mass or more, or 0.01% by mass or more, and may be 20% by mass or less, 10% by mass or less, 5% by mass or less, or 0.1% by mass or less. The granular powder of the present embodiment may not contain an additive component such as alumina (i.e., the content of the additive component is 0% by mass), but may contain alumina, and the content of alumina may be more than 0% by mass and 20% by mass or less, 0.01% by mass or more and 10% by mass or less, or 0.01% by mass or more and 0.1% by mass or less. The content of the additive component in the granular powder of this embodiment is determined from the mass ratio [mass%] of the additive component converted into oxide to the mass of the granular powder converted into oxide (hereinafter also referred to as "oxide mass"). 2 O 3 , silica is SiO 2 and Germania is GeO 2 It is.

[0034] The granular powder of this embodiment may contain a pigment component. By containing the pigment component, the granular powder of this embodiment becomes a raw material for obtaining a sintered body of any color tone. The pigment component may be any compound capable of coloring ceramics, and examples thereof include transition metal oxides and composite oxides of transition metals. Examples of transition metal oxides include oxides of transition metals other than zirconium and hafnium, and oxides containing one or more selected from the group consisting of titanium (Ti), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), niobium (Nb), palladium (Pd), and tungsten (W). Examples of composite oxides of transition metals include composite oxides containing two or more selected from the group consisting of titanium, vanadium, manganese, iron, cobalt, nickel, and copper, and composite oxides containing two or more selected from the group consisting of manganese, iron, cobalt, and nickel, and two or more selected from the group consisting of aluminum (Al), zinc (Zn), germanium (Ge), gadolinium (Gd), and tin (Pb). The shape of the pigment component contained in the granular powder of this embodiment is arbitrary, but may be a powder (or powder particles).

[0035] The type and content of the pigment components may be any combination and content that results in a desired color tone. The granular powder of this embodiment may not contain a pigment component (i.e., the content of the pigment component is 0% by mass), but may contain a pigment component and the content of the pigment component may be more than 0% by mass and not more than 10% by mass, 0.01% by mass or more and not more than 1% by mass, or 0.01% by mass or more and not more than 0.5% by mass. The content of the pigment component in the granular powder of this embodiment is determined from the mass ratio [mass %] of the pigment component converted into oxide relative to the oxide mass.

[0036] The granular powder of the present embodiment may contain unavoidable impurities. Examples of unavoidable impurities in zirconia include hafnia (HfO 2 In this embodiment, when determining values ​​based on the composition such as the content, hafnia may be calculated assuming that it is zirconia.

[0037] The granular powder of this embodiment contains a binder. Compared with a molded body not containing a binder, the molded body obtained by molding the granular powder of this embodiment has high strength. The binder may be a binder that can be applied to the ceramic powder used in dry press molding, and may further be a binder that can improve the properties of the molded body obtained by dry press molding of the ceramic powder. Examples of such binders include one or more selected from the group consisting of polyvinyl alcohol resins, polyvinylpyrrolidone resins, and acrylic resins. Since the storage properties of the obtained powder and molded body are improved and the crushability during molding is excellent, the binder is preferably at least one of polyvinylpyrrolidone resins and acrylic resins, and more preferably acrylic resins. The binder contained in the granular powder of this embodiment may be a commercially available binder for press molding (for example, the Serander series, manufactured by HighChem Co., Ltd.; AS-1800, AS-2000, manufactured by Toa Gosei Co., Ltd., etc.).

[0038] The binder content of the granular powder of this embodiment may be 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more. As a result, if the binder content is within this range, a molded body having high strength can be obtained. In addition, the binder content may be an amount that can be sufficiently segregated on the granule surface, for example, 8% by mass or less, 6% by mass or less, 4% by mass or less, 3.5% by mass or less, or 3% by mass or less, and is preferably 0.1% by mass or more and 8% by mass or less, 0.5% by mass or more and 6% by mass or less, 1% by mass or more and 4% by mass or less, 1% by mass or more and 3.5% by mass or less, or 1% by mass or more and 3% by mass or less. As the binder content increases, the density of the obtained molded body tends to increase.

[0039] In this embodiment, the binder content can be determined from the ratio [mass %] of the mass reduction after heat treatment of the granular powder of this embodiment when the granular powder is heat treated under the following conditions, relative to the mass of the granular powder of this embodiment. Heat treatment atmosphere: Air Heat treatment temperature: 400℃ Heat treatment time: 5 hours Heating rate: 50℃ / hour

[0040] The heat treatment may be carried out in a general muffle furnace (for example, FO310, manufactured by Yamato Chemical Co., Ltd.) Prior to the heat treatment, the granular powder may be pretreated by drying in an air atmosphere at 110° C. for 1 hour.

[0041] The granular powder of the present embodiment may contain one or more selected from the group consisting of a dispersant, a lubricant, a plasticizer, and an antifoaming agent, provided that the effects of the granular powder are not impaired, but may not contain these.

[0042] The composition of the granular powder of this embodiment includes, for example, a binder, alumina, and AB as a pigment component. 2 O 4 The composition of the granular powder made of the spinel oxide and yttrium-stabilized zirconia containing iron can be determined from the following: In the spinel oxide, A is a divalent metal element, and B is a trivalent metal element. Amount of oxidized substance [g] = Al 2 O 3 +AB 2 O 4 +Fe 2 O 3 +Y 2 O 3 +ZrO 2 Alumina content [mass%] = {Al 2 O 3 / (Al 2 O 3 +AB 2 O 4 +Fe 2 O 3 +Y 2 O 3 +ZrO 2 )}×100 Pigment content [mass%] = {(AB 2 O 4 +Fe 2 O 3 ) / (Al 2 O 3 +AB 2 O 4 +Fe 2 O 3 +Y 2 O 3+ZrO 2 )}×100 Iron content [mass%]={Fe 2 O 3 / (Al 2 O 3 +AB 2 O 4 +Fe 2 O 3 +Y 2 O 3 +ZrO 2 )}×100 Spinel oxide content [mass%] = {AB 2 O 4 / (Al 2 O 3 +AB 2 O 4 +Fe 2 O 3 +Y 2 O 3 +ZrO 2 )}×100 Stabilizing element amount [mol%]={Y 2 O 3 / (Y 2 O 3 +ZrO 2 )}×100

[0043] The amount of binder is calculated by the above-mentioned method. Due to the difference in the calculation method, the mass percentage of the granular powder in this embodiment may differ from 100% by mass when the binder is taken into consideration (the binder may be treated as an external number).

[0044] The granular powder of this embodiment has a wavelength of 1730±20 cm in the infrared spectrum per mass of the binder. -1 The absorption peak intensity (hereinafter, simply referred to as "unit absorption peak intensity") having a peak top at 1730±20 cm in the infrared spectrum is 0.023 counts or more. When the unit absorption peak intensity shows such a value, chipping of the obtained molded body is unlikely to occur. One of the reasons for this is thought to be that the state of the binder in the granular powder of this embodiment is different from that of conventional granular powders. That is, -1The absorption peak having a peak top (hereinafter, also referred to as "binder peak") is considered to correspond to a peak derived from the binder. In addition, a high binder peak relative to the mass of the binder in the granular powder is considered to indicate that a large amount of binder is present on the surface of the particles (granular particles) constituting the granular powder. Therefore, the granular powder of this embodiment is considered to be a granular powder composed of granular particles having a structure in which the binder content on the surface is high relative to the binder content inside. This makes it easier for the binder between the granular particles to adhere to each other when pressure is applied. As a result, it is considered that defects are less likely to occur even at the ends of the obtained molded body, and the strength is high.

[0045] The unit absorption peak intensity may be 0.023 counts or more, and is preferably 0.025 counts or more or 0.028 counts or more. It is considered that the higher the unit absorption peak intensity, the higher the binder ratio on the surface of the granular particles constituting the granular powder, and the stronger the molded body obtained is likely to be. It is considered that the granular particles constituting the granular powder of this embodiment are granular particles having a higher amount of binder on the surface of the granular particles compared to the amount of binder inside the granular particles. That is, the binder concentration decreases from the surface of the granular particles toward the inside of the granular particles, and the granular powder is made of granular particles having a gradient composition of binder content. In addition, when the unit absorption peak intensity is high, the maximum strain described below tends to be high, and the granular powder is likely to have excellent moldability.

[0046] On the other hand, the unit absorption peak intensity does not need to be excessively high, and may be 0.045 count or less, 0.042 count or less, 0.040 count or less, or 0.035 count or less. The unit absorption peak intensity of the granular powder of this embodiment is preferably 0.023 count or more and 0.045 count or less, 0.028 count or more and 0.042 count or less, or 0.028 count or more and 0.040 count or less. Since the granular compressibility (described later) of the granular powder of this embodiment is particularly likely to be high, the unit absorption peak intensity is preferably more than 0.028 count, more preferably more than 0.028 count and 0.040 count or less, and even more preferably more than 0.029 count and 0.036 count or less.

[0047] The infrared spectrum in this embodiment is a value measured by a single reflection ATR method under the following conditions: The single reflection ATR method may be performed using a general Fourier transform infrared spectrophotometer (e.g., IRXross, manufactured by Shimadzu Corporation) and a single reflection total reflection measurement device integrated with a sample chamber (e.g., QATR-10, manufactured by Shimadzu Corporation). Disassembly: 4cm -1 Number of times: 40 Wave number range: 4000~1500cm -1 Apodization function: SqrTriangle

[0048] The measurement sample should be a granular powder attached to a diamond prism with a diameter of 2 mm.

[0049] The unit absorption peak intensity may be calculated from the obtained infrared spectrum according to the following formula:

[0050] D uni = (D 1 -D ref ) / W In the above formula, D uni is the unit of absorbance peak intensity [count], D 1 is the measurement sample's 1730±20cm -1The peak intensity [count] of the peak having the peak top at D ref is the standard sample's 1730±20cm -1 and W is the content of the binder in the sample [mass%]. -1 When there are multiple peaks with a peak top at the peak intensity, the intensity of the peak with the maximum peak intensity should be used. The standard sample is a commercially available zirconia granular powder (product name: TZ-3YS, manufactured by Tosoh Corporation).

[0051] The shape of the granular particles constituting the granular powder of this embodiment is arbitrary, and the granular powder of this embodiment may be composed of granular particles having one or more shapes selected from the group consisting of amorphous, spherical, approximately spherical, and elliptical, and further one or more shapes selected from the group consisting of spherical, approximately spherical, and elliptical. Furthermore, the granular powder of this embodiment may contain granular particles having a spherical, approximately spherical, or elliptical shape having a depression, or may contain granular particles having a crushed shape of these.

[0052] The average granule size of the granular powder of this embodiment is 30 μm or more, or 40 μm or more, and may be 80 μm or less, 60 μm or less, or 50 μm or less, and is preferably 30 μm or more and 80 μm or less, 40 μm or more and 60 μm or more, or 40 μm or more and 50 μm or less. By having such an average granule size, the density of the molded body obtained by press molding it tends to be high.

[0053] The granular powder of this embodiment has a light bulk density of 1.10 g / cm 3 More than 1.20g / cm 3 or more than 1.25g / cm 3 More than 1.50g / cm 3 Less than or equal to 1.35g / cm 3 The following are listed as being below: 1.10 g / cm 3 More than 1.50g / cm 3 Below 1.20g / cm 3 More than 1.35g / cm 3 Less than or equal to 1.25g / cm 3 More than 1.35g / cm3 It is preferable that:

[0054] The granular powder of this embodiment preferably has high moldability. When 15±0.5 g of the granular powder is filled into a cylindrical mold having a diameter of 25 mm and press molded at a pressure of 49 MPa, the measured density (hereinafter also referred to as "molded density") is 2.70 g / cm. 3 More than 2.80g / cm 3 or more than 2.85g / cm 3 More than 3.20g / cm 3 Below 3.00g / cm 3 Less than or equal to 2.90g / cm 3 The following are listed as being below: 2.70 g / cm 3 More than 3.20g / cm 3 Below 2.80g / cm 3 More than 3.00g / cm 3 Less than or equal to 2.85g / cm 3 More than 2.90g / cm 3 It is preferable that the unit absorption peak intensity is satisfied and the molding density is 2.80 g / cm or less. 3 More than 2.90g / cm 3 The granular powder of this embodiment described below can provide a molded article having strength that is less prone to defects, even when compared with a granular powder that does not satisfy the unit absorption peak intensity and has a higher molding density.

[0055] The granular powder of this embodiment preferably has a strength that does not crumble during handling and is easily compressed during press molding. The strength of the granular powder of this embodiment (hereinafter also referred to as "granular strength") is preferably 0.1 MPa or more, 0.4 MPa or more, or 0.5 MPa or more, and is preferably 2 MPa or less, 1.5 MPa or less, 1.2 MPa or less, or 1.0 MPa or less. The granular strength of the granular powder of this embodiment can be 0.1 MPa or more and 2 MPa or less, 0.1 MPa or more and 1.2 MPa or less, or 0.4 MPa or more and 1.0 MPa or less. In addition, by having a strength of 0.4 MPa or more and 0.5 MPa or less, a molded body that is less prone to defects can be obtained.

[0056] Granule strength is the strength at which a granular powder is crushed, and is a value determined by a method conforming to JIS R 1639-5. Specifically, it may be measured by the following method using a general device (e.g., MCT-510, manufactured by Shimadzu Corporation). That is, 10 samples of granular particles constituting the granular powder are extracted, and the longest and shortest lengths of each granular particle are measured at an objective lens magnification of 10 times using a length measuring kit attached to the measuring device, and the average is regarded as the granular particle size (deemed granular particle size). Next, a stress-strain curve is measured while pressing an indenter against each granular particle under the following conditions.

[0057] Indenter: FLAT200 Test force: 30mN Load speed: 30(0.1487mN / sec) From the inflection point of the obtained stress-strain curve, the granule strength of each granule particle is calculated by the following formula, and the average value is taken as the granule strength of the granule powder.

[0058] CS=2.48×[{CS 1 / (πD 1 2 )+CS 2 / (πD 2 2 )+ +CS 10 / (πD 10 2 )} / 10] In the above formula, CS is the granule strength [MPa], CS 1 ~CS 10 is the compressive strength of each granule particle [mN], and D 1 or D 10 is the assumed granule diameter [μm] of each granule particle.

[0059] The granular powder of this embodiment preferably has a granular compression ratio of 0.1% or more, 2% or more, 5% or more, or 6% or more, and preferably 15% or less, 12% or less, or 10% or less. The granular compression ratio of the granular powder of this embodiment can be, for example, 0.1% to 15% or less, 2% to 12% or less, 5% to 12% or less, 6% to 12% or less, or 6% to 10% or less. This makes it easier to obtain a tough molded body, and the obtained molded body is less likely to break.

[0060] The granule compressibility can be calculated from the stress-strain curve obtained by the same measuring method as for the granule strength, according to the following formula: Granule compression ratio = Indenter displacement when crushing granules / granule diameter C={(C 1 / D 1 +C 2 / D 2 +···+C 10 / D 10 ) / 10}×100 In the above formula, C is the granule compression rate [%], C 1 ~C 10 is the distance traveled by the indenter from the zero point (initial position) to the inflection point in the stress-strain curve of each granule particle [μm], and D 1 or D 10 is the assumed granule diameter [μm] of each granule particle.

[0061] The granular powder of this embodiment preferably satisfies at least one of the following: a granular strength of more than 0.3 MPa and a granular compression ratio of 6% or more. This results in a powder with high handleability, and the resulting molded body is less likely to have defects. In addition, since the powder tends to have high crushability, the granular powder of this embodiment preferably has a granular strength of 0.3 MPa or more and a granular compression ratio of 6% or more, preferably has a granular strength of 0.4 MPa or more and a granular compression ratio of 6% or more, and more preferably has a granular strength of 0.5 MPa or more and a granular compression ratio of 6% or more.

[0062] [Method of manufacturing granular powder] A preferred method for producing the granular powder of this embodiment includes a method for producing the granular powder, which includes a step of spray-drying a slurry containing ceramic powder, a binder, and a solvent by setting the difference between the hot air temperature and the exhaust air temperature to at least 55° C. This provides the granular powder of this embodiment, which produces a molded product that is less prone to defects such as cracks and chips.

[0063] In the step of spray-drying the slurry containing the ceramic powder, binder and solvent by setting the difference between the hot air temperature and the exhaust air temperature at 55° C. or more (hereinafter also referred to as the "spray-drying step"), the slurry containing the ceramic powder, binder and solvent (hereinafter also referred to as the "raw material slurry") is provided. The ceramic powder and binder contained in the raw material slurry may be any suitable one depending on the purpose, and may be any one of the ceramic powder and binder types described above.

[0064] In addition, the BET specific surface area of ​​the ceramic powder contained in the slurry is 5m 2 / g or more or 6m 2 / g or more, and 25m 2 / g or less or 20m 2 / g or less, and 5m 2 / g or more 25m 2 / or less, or 6m 2 / g or more 20m 2 It is preferable that the molecular weight is not more than 1 / g.

[0065] The ceramic powder may have any particle size that allows it to be formed into granules by drying, and examples of such particle sizes include 0.05 μm to 1.5 μm, and further 0.1 μm to 0.5 μm.

[0066] The solvent contained in the raw material slurry may be any solvent in which the ceramic powder and binder are uniformly dispersed, and examples of the solvent include at least one of an aqueous solvent and a non-aqueous solvent, at least one of water and alcohol, or at least one of water and ethanol, with water being preferred.

[0067] The raw material slurry may contain, in addition to the ceramic powder, binder, and solvent, one or more selected from the group consisting of the additive components, pigment components, dispersants, lubricants, plasticizers, and antifoaming agents described above.

[0068] In this embodiment, "spray drying" refers to an operation in which the raw material slurry in the form of droplets is brought into contact with a high-temperature carrier gas to rapidly evaporate the solvent, thereby removing the solvent from the droplets of the raw material slurry, and obtaining a granular powder composed of granular particles containing ceramic powder and a binder. Spray drying is performed using a spray dryer. In this embodiment, spray drying can be performed by forming the raw material slurry into droplets and introducing them into the spray dryer together with a high-temperature carrier gas, and recovering the obtained granular powder from the spray dryer together with the carrier gas.

[0069] In the spray drying process, the difference between the hot air temperature and the exhaust air temperature (hereinafter also referred to as the "inlet / outlet temperature difference") is set to 55°C or more to perform spray drying. This results in a granular powder composed of granular particles having a structure in which the binder content on the surface is higher than the binder content inside. In spray drying, the solvent of the raw material slurry is evaporated instantly. For this reason, a hot air temperature suitable for removing the solvent, that is, the introduction temperature (inlet temperature) of the carrier gas into the spray dryer, was conventionally set. On the other hand, the obtained granular powder is carried by the carrier gas and collected, but the temperature of the carrier gas decreases as it passes through the spray dryer. For this reason, the exhaust air temperature, that is, the discharge temperature (outlet temperature) of the carrier gas from the spray dryer, was not controlled with a purpose, such as being set to an arbitrary temperature according to the size of the spray dryer. In contrast, in this embodiment, it was found that the state of the binder changes while the granular powder is carried by the carrier gas, and further, by setting the inlet / outlet temperature difference to a certain temperature or more, most of the solvent is instantly removed, but the diffusion of the binder in each granular particle constituting the granular powder is promoted with the removal of the remaining solvent. As a result, it was found that a granular powder composed of granular particles having a structure in which the binder content on the surface is higher than the binder content inside can be obtained. The inlet / outlet temperature difference may be 55°C or more, and is preferably 60°C or more or 80°C or more. On the other hand, the upper limit of the inlet / outlet temperature difference can be 150°C or less, 120°C or less, or 100°C or less. The inlet / outlet temperature difference is preferably 55°C or more and 150°C or less, 60°C or more and 120°C or less, 80°C or more and 120°C or less, or 80°C or more and 100°C or less.

[0070] The inlet / outlet temperature difference can be controlled by adjusting the hot air temperature and exhaust air temperature using the temperature control function of the spray dryer.

[0071] The hot air temperature may be any temperature at which the solvent is removed from the raw material slurry, and may be 120°C or higher, 150°C or higher, over 150°C or over 180°C, and may be 300°C or lower, 250°C or lower, or 200°C or lower. Examples of the hot air temperature include 120°C or higher and 300°C or lower, 120°C or higher and 250°C or lower, 150°C or higher and 200°C or lower, over 150°C or lower and 250°C or lower, or 180°C or higher and 200°C or lower. By setting the hot air temperature within this range and being moderately low (for example, 210°C or lower), the amount of solvent that evaporates instantaneously is suppressed, and the diffusion of the binder in each granule particle that constitutes the granule powder due to the removal of the remaining solvent is further promoted. This makes it easier for the binder concentration difference between the surface of the granule particle and the inside of the granule particle to become larger, and as a result, the strength of the resulting molded body is easily increased.

[0072] The exhaust air temperature may be any temperature that results in the inlet / outlet temperature difference described above, and may be lower than the hot air temperature, and may be 65°C or more, 95°C or more, over 100°C or 105°C or more, and may be 245°C or less, 195°C or less, 145°C or less, or 120°C or less, for example 65°C or more and 245°C or less, 65°C or more and 195°C or less, 95°C or more and 145°C or less, 105°C or more and 145°C or less, or 105°C or more and 120°C or less.

[0073] The carrier gas in the spray drying may be, for example, one or more selected from the group consisting of nitrogen, argon, and air, and is preferably air.

[0074] The spraying method in the spray drying may be any method as long as the raw material slurry is turned into droplets, but at least one of the spraying methods using an atomizer or a spray nozzle may be used. A spraying method in which the raw material slurry is turned into droplets using an atomizer disk is preferred because it produces granular powder with a narrow particle size distribution. [Methods of manufacturing the green body, calcined body and sintered body] The granular powder of the present embodiment can be used as a precursor of a molded body, a calcined body, and a sintered body. For example, the granular powder of the present embodiment can be used in a method for producing a molded body, which includes a step of molding the granular powder of the present embodiment.

[0075] A molded body is obtained by a process of molding the granular powder of this embodiment (hereinafter also referred to as a "molding process"). The molding method may be one or more selected from the group consisting of known molding methods, press molding, cold isostatic pressing, injection molding, slip casting, and slip casting molding, and the molding method in the molding process is preferably press molding. In addition, cold isostatic pressing may be performed after press molding.

[0076] The conditions of the press molding may be any conditions according to the purpose, but for example, molding may be performed at a molding pressure of 15 MPa or more and 100 MPa or less, and the molding pressure may be maintained while being applied. This allows the granular powder of this embodiment to be appropriately crushed, making it easier to obtain a molded body with high strength. In this case, the holding time can be, for example, 5 seconds or more and 60 seconds or less.

[0077] The molded body obtained from the granular powder of this embodiment preferably has a strength that is unlikely to cause chipping during handling. As one of the indicators of strength during handling, a molded body obtained by filling 15±0.5 g of the granular powder into a cylindrical mold having a diameter of 25 mm and uniaxially press-molding the molded body at a pressure of 49 MPa is used as a measurement sample, and the strength (hereinafter also referred to as "chipping strength") is measured using a general autograph (for example, AGS-10KNX STD 0.5 class, manufactured by Shimadzu Corporation) equipped with a 10 kN load cell. This makes it possible to confirm the likelihood of defects occurring in the molded body obtained from the granular powder. The chipping strength is determined by applying a 1.8 mm diameter indenter along the circumferential direction of the measurement sample and applying a load at 0.1 mm / min to obtain the pressure at the maximum load. Five points are measured for one molded body, and the average value obtained is taken as the chipping strength. The distance traveled by the indenter at this time is taken as the "maximum strain". The maximum strain is one of the indicators indicating the toughness of the molded body. The larger the maximum strain, the less likely the molded body is to break. The maximum strain of the molded body obtained from the granular powder of this embodiment is preferably more than 0.05 mm, and more preferably 0.06 mm or more or 0.08 mm or more. The upper limit of the maximum strain can be 0.25 mm or less, 0.20 mm or less, 0.16 mm or less, 0.15 mm or less, or 0.12 mm or less. The maximum strain of the molded body obtained from the granular powder of this embodiment can be exemplified as more than 0.05 mm and 0.25 mm or less, 0.06 mm or more and 0.20 mm or less, 0.06 mm or more and 0.15 mm or less, 0.08 mm or more and 0.16 mm or less, or 0.08 mm or more and 0.12 mm or less.

[0078] The density of the molded body obtained from the granular powder of this embodiment may be an actually measured density similar to the above-mentioned molded density.

[0079] The chipping strength of the molded body obtained from the granular powder of this embodiment is 11 MPa or more, 13 MPa or more, or 14 MPa or more, and can be 25 MPa or less, 18 MPa or less, or 15 MPa or less, for example, 11 MPa or more and 25 MPa or less, or 13 MPa or more and 18 MPa or less.

[0080] The molded body obtained from the granular powder of this embodiment can be used in a method for producing a calcined body. The calcined body can be obtained by a method for producing a calcined body, which includes a step of calcining the molded body. The calcination may be a heat treatment at a temperature at which the molded body has a strength suitable for processing, or a temperature lower than the temperature at which the densification of ceramics progresses, and may be a heat treatment in an air atmosphere at 800°C or higher and lower than 1200°C, or even at 1000°C or higher and 1150°C or lower. The calcination time may be appropriately adjusted depending on the size of the molded body to be subjected to calcination and the performance of the calcination furnace, and may be, for example, 30 minutes to 5 hours, or 1 hour to 3 hours.

[0081] The molded body obtained from the granular powder of this embodiment, or the calcined body obtained from the sintered body, can be used in a method for producing a sintered body. The sintered body can be produced by a production method having a step of sintering at least one of the molded body and the calcined body. Sintering may be a heat treatment at a temperature at or above the temperature at which densification of ceramics progresses, and is preferably atmospheric sintering, and more preferably heat treatment in an air atmosphere at 1200°C to 1700°C, and more preferably at 1400°C to 1550°C. The sintering time may be appropriately adjusted depending on the size of the molded body to be sintered and the performance of the sintering furnace, and may be, for example, 10 minutes to 5 hours, or 1 hour to 3 hours. EXAMPLES

[0082] The present disclosure will be specifically described below with reference to examples and comparative examples. However, the present disclosure is not limited to these examples.

[0083] (BET specific surface area) The BET specific surface area was measured using an automatic specific surface area / pore distribution measuring device (device name: Tristar II 3020, manufactured by Shimadzu Corporation) by the BET multipoint method (5 points) in accordance with JIS R 1626. Prior to the measurement, the powder sample was pretreated by degassing in the air at 250°C for 1 hour or more and less than 12 hours. Adsorption medium:N 2 Adsorption temperature: -196℃ Pretreatment conditions: Degassing in air at 250℃ for 1 hour or more

[0084] (Average particle size) The average granule size was measured by a dry method. That is, a particle size distribution meter (product name: MT3100II, manufactured by Microtrack Bell) was used to measure the volume particle size distribution curve of the granule powder under the following conditions. The particle size (median size) corresponding to a volume ratio of 50% on the obtained cumulative volume particle size distribution curve was taken as the average granule size. Measurement sample: Granular powder Refractive index of zirconia: 2.17 Refractive index of air: 1.333 Measurement time: 10 seconds

[0085] (Lightweight bulk density) The granular powder was passed through a sieve with a mesh size of 500 μm. The granular powder that had passed through the sieve was then allowed to fall freely from a height of 35 mm to a volume of 100 cm. 3 The powder was filled into the container. 3 I used enough to overflow the 100cm container. 3 The top surface of the container was leveled using a leveling plate to remove the powder that had overflowed from the container. 3 The mass of the container was measured using a balance, and the mass and lightly packed bulk density of the filled granular powder were calculated by subtracting the mass of the container.

[0086] (Infrared spectrum measurement) The infrared spectrum was measured under the following conditions using a Fourier transform infrared spectrophotometer (instrument name: IRXross, manufactured by Shimadzu Corporation) and a sample chamber integrated single reflection type total reflection measurement apparatus (QATR-10, manufactured by Shimadzu Corporation).

[0087] Disassembly: 4cm -1 Number of times: 40 Wave number range: 4000~1500cm -1 Apodization function: SqrTriangle The measurement sample was a granular powder attached to a diamond prism with a diameter of 2 mm.

[0088] From the obtained infrared spectrum, the unit absorption peak intensity was calculated according to the following formula.

[0089] D uni = (D 1 -D ref ) / W In the above formula, D uni is the unit of absorbance peak intensity [count], D 1 is the measurement sample's 1730±20cm -1 The peak intensity [count] of the peak having the peak top at D ref is the standard sample (TZ-3YS, Tosoh Corporation) of 1730±20cm -1 and W is the content of the binder in the sample [mass%]. -1 When there are multiple peaks with a peak top in the range, the intensity of the peak with the maximum peak intensity was used.

[0090] (granule strength) Granule strength was determined by a method conforming to JIS R 1639-5. That is, 10 samples of granule particles constituting the granule powder were extracted. Using a length measuring kit attached to a measuring device (MCT-510, manufactured by Shimadzu Corporation), the longest and shortest lengths of each extracted granule particle were measured at an objective lens magnification of 10 times, and the average was regarded as the granule particle size (deemed granule particle size). Next, a stress-strain curve was measured while pressing an indenter against each granule particle under the following conditions.

[0091] Indenter: FLAT200 Test force: 30mN Load speed: 30(0.1487mN / sec) From the inflection point of the obtained stress-strain curve, the granule strength of each granule particle was calculated according to the following formula, and the average value was regarded as the granule strength of the granule powder.

[0092] CS=2.48×[{CS 1 / (πD 1 2 )+CS 2 / (πD 2 2 )+ +CS 10 / (πD 10 2 )} / 10] In the above formula, CS is the granule strength [MPa], CS 1 ~CS 10 is the compressive strength of each granule particle [mN], and D 1 or D 10 is the assumed granule diameter [μm] of each granule particle.

[0093] (Granule compression ratio) The granule compressibility was calculated from the stress-strain curve obtained by the same measuring method as for the granule strength, according to the following formula:

[0094] Granule compression ratio = Indenter displacement when crushing granules / granule diameter C={(C 1 / D 1 +C 2 / D 2 +···+C 10 / D 10 ) / 10}×100 In the above formula, C is the granule compression rate [%], C 1 ~C 10 is the distance traveled by the indenter from the zero point (initial position) to the inflection point in the stress-strain curve of each granule particle [μm], and D 1 or D 10 is the assumed granule diameter [μm] of each granule particle.

[0095] (chipping strength and maximum strain) An autograph (device name: AGS-10KNX STD 0.5 class, manufactured by Shimadzu Corporation) equipped with a 10 kN load cell was used. 15±0.5 g of granular powder was filled into a cylindrical mold with a diameter of 25 mm, and a compact was obtained by uniaxial press molding at a pressure of 49 MPa, which was used as the measurement sample. An indenter with a diameter of 1.8 mm was applied along the circumferential direction of the measurement sample, and the pressure at the maximum load when a load was applied at 0.1 mm / min was obtained, and the average value of five points was used as the chipping strength. The travel distance of the indenter at that time was used as the maximum strain.

[0096] (Molded body density) 15±0.5 g of the granular powder was filled into a cylindrical mold with a diameter of 25 mm, and a compact was obtained by uniaxial press molding at a pressure of 49 MPa. The mass of the obtained compact sample was measured with a balance, and the volume was measured with a vernier caliper to obtain the dimensions. The actual density was calculated from the obtained mass and volume, and this was taken as the compact density.

[0097] Example 1 A slurry containing alumina-containing yttrium-stabilized zirconia powder and pure water, in which the amount of alumina is 0.05 mass% and the amount of yttrium is 5.5 mol%, and a slurry containing alumina-containing yttrium-stabilized zirconia powder and pure water, in which the amount of alumina is 0.05 mass% and the amount of yttrium is 2.5 mol%, were mixed so that the amount of yttrium was 4.0 mol%, to obtain a mixed slurry. The BET specific surface area of ​​the powder in the mixed slurry was 10.1 m 2 / g.

[0098] The mixed slurry was mixed with 2.0% by mass of an acrylic binder as a binder and pure water to obtain a dry slurry with a solid content concentration (mass ratio of powder in the mixed slurry) of 40% by mass. The dry slurry was granulated and dried using an atomizer-type spray dryer equipped with a pin-shaped disk at a hot air temperature (inlet temperature) of 200°C and an exhaust air temperature (outlet temperature) of 105°C (inlet / outlet temperature difference 95°C), to obtain a granular powder made of yttrium-stabilized zirconia containing an acrylic binder and alumina with a binder content of 2.0% by mass, alumina content of 0.05% by mass, and yttrium content of 4.0 mol%, which was used as the granular powder of this example. The loose bulk density of the granular powder of this example was 1.22 g / cm 3 The granule strength was 0.4 MPa and the granule compression rate was 6.1%.

[0099] Comparative Example 1 A granular powder made of yttrium-stabilized zirconia containing an acrylic binder and alumina, in which the binder amount was 2.0 mass%, the alumina amount was 0.05 mass%, and the yttrium amount was 4.0 mol%, was obtained by the same method as in Example 1, except that the dried slurry was granulated and dried with a hot air temperature of 150°C and an exhaust air temperature of 100°C (inlet / outlet temperature difference: 50°C). The granular powder of this comparative example had a granule strength of 0.3 MPa and a granule compression rate of 5.5%.

[0100] Example 2 A granular powder made of yttrium-stabilized zirconia containing an acrylic binder and alumina, with a binder content of 3.4 mass%, alumina content of 0.05 mass%, and yttrium content of 4.0 mol%, was obtained in the same manner as in Example 1, except that the mixed slurry, acrylic binder, and pure water were mixed so that the acrylic binder content was 3.4 mass%, to obtain a dry slurry, and this was used as the granular powder of this example. The loose bulk density of the granular powder of this example was 1.28 g / cm. 3 The granule strength was 0.3 MPa and the granule compression rate was 7.9%.

[0101] An SEM image of the granular powder of this example is shown in Figure 1. The granular powder of this example contained, in addition to granular particles having a substantially spherical shape, substantially spherical granular particles having depressions, and granular particles having a crushed substantially spherical shape.

[0102] Example 3 A granular powder made of yttrium-stabilized zirconia containing an acrylic binder and alumina with a binder content of 2.0 mass%, alumina content of 0.05 mass%, and yttrium content of 4.0 mol% was obtained by the same method as in Example 1, except that the mixed slurry, acrylic binder, and pure water were mixed to obtain a dry slurry so that the acrylic binder content was 2.0 mass%, and the dry slurry was granulated and dried with a hot air temperature of 220°C and an exhaust air temperature of 105°C (inlet / outlet temperature difference: 115°C). This was used as the granular powder of this example.

[0103] The results are shown in Table 1.

[0104] [Table 1]

[0105] Example 1 and Comparative Example 1 have the same composition. Nevertheless, it was confirmed that Example 1, in which the inlet / outlet temperature difference is 95°C, has a high chipping strength compared to Comparative Example 1, in which the inlet / outlet temperature difference is 50°C, and that a molded body that is less likely to have defects during handling can be obtained in the Example. Furthermore, it was confirmed that the granular powder of Example 1 has a large maximum strain compared to the granular powder of Comparative Example 1, and is a granular powder with high crushability by press molding. It was also confirmed that the granular powder of Example 2, which has a high binder content, has a higher molded body density compared to Example 1. It was also confirmed that Example 1, in which the hot air temperature is lower than Example 3, has a higher chipping strength.

[0106] Example 4 A mixed slurry was obtained by mixing an alumina-containing yttria-stabilized zirconia powder having an alumina content of 0.25% by mass and an yttria content of 3.0 mol% with pure water. The mixed slurry, the acrylic binder, and pure water were mixed so that the acrylic binder was 5.0% by mass to obtain a dried slurry having a solid content of 48%, and the dried slurry was granulated and dried with a hot air temperature of 185°C and an exhaust air temperature of 125°C (inlet / outlet temperature difference: 60°C). A granular powder was obtained from yttrium-stabilized zirconia containing an acrylic binder and alumina, with a binder content of 5.0% by mass, an alumina content of 0.25% by mass, and an yttrium content of 3.0 mol%, and this was used as the granular powder of this example.

[0107] The granular powder of this example had an average granular particle size of 42 μm, a unit absorption peak intensity of 0.038 count, a granular strength of 0.5 MPa, and a granular compressibility of 13.2%.

[0108] Example 5 Alumina-containing yttrium-stabilized zirconia powder with an alumina content of 0.05 mass% and an yttrium content of 3.0 mol% was mixed with pure water to obtain a slurry. The BET specific surface area of ​​the powder in the obtained slurry was 12.8 m 2 / g.

[0109] The obtained slurry was mixed with 2.0 mass% of an acrylic binder and pure water to obtain a dry slurry with a solid content concentration of 40 mass%. In the same manner as in Example 1, except that, a granular powder made of yttrium-stabilized zirconia containing an acrylic binder and alumina with a binder content of 2.0 mass%, alumina content of 0.05 mass%, and yttrium content of 3.0 mol% was obtained, and this was used as the granular powder of this example.

[0110] The granular powder of this example had an average granular particle size of 45 μm and a unit absorption peak intensity of 0.028 count.

[0111] In addition, the green density and maximum strain of the granular powder of this example were similar to those of Example 1, and were 2.85 g / cm 3 and 0.07 mm.

[0112] Example 6 Alumina-containing yttrium-stabilized zirconia powder with an alumina content of 0.05 mass% and an yttrium content of 5.5 mol% was mixed with pure water to obtain a slurry. The BET specific surface area of ​​the powder in the obtained slurry was 9.7 m 2 / g.

[0113] The obtained slurry was mixed with 2.0 mass% of an acrylic binder and pure water to obtain a dry slurry with a solid content concentration of 40 mass%. In the same manner as in Example 1, except that, a granular powder made of yttrium-stabilized zirconia containing an acrylic binder and alumina with a binder content of 2.0 mass%, alumina content of 0.05 mass%, and yttrium content of 5.5 mol% was obtained, and this was used as the granular powder of this example.

[0114] The granular powder of this example had an average granular particle size of 43 μm, a unit absorption peak intensity of 0.029 count, a granular strength of 0.3 MPa, and a granular compressibility of 6.5%.

[0115] In addition, the green density and maximum strain of the granular powder of this example were similar to those of Example 1, and were 2.84 g / cm 3 and 0.07 mm.

[0116] Example 7 Alumina-containing yttrium-stabilized zirconia powder (product name: 3YS-E, manufactured by Tosoh Corporation) having an alumina content of 0.25 mass% and an yttrium content of 3.0 mol% and a Co-Al-Fe-Zn composite oxide as a black pigment were mixed with pure water to obtain a slurry.

[0117] The obtained slurry was mixed with 5.0% by mass of an acrylic binder and pure water to obtain a dried slurry with a solid content concentration of 48% by mass, and the dried slurry was granulated and dried at a hot air temperature of 210°C and an exhaust air temperature of 110°C (inlet / outlet temperature difference of 100°C) in the same manner as in Example 1, except that a granular powder consisting of an acrylic binder, alumina, and a Co-Al-Fe-Zn composite oxide with a binder content of 5.0% by mass, an alumina content of 0.25% by mass, and an yttrium content of 3.0 mol% was obtained, which was used as the granular powder of this example. The granular powder of this example had an average granular particle size of 42 μm, a unit absorption peak intensity of 0.035 count, a granular strength of 0.5 MPa, and a granular compression rate of 11.5%.

[0118] Furthermore, the granular powder of this example had a chipping strength of 14.9 MPa and a maximum distortion of 0.15 mm, and it was confirmed that the greater the amount of binder, the more susceptible the powder to distortion.

Claims

1. Ceramic powder and a binder are included, and the infrared spectrum of 1730 ± 20 cm per mass of the binder is -1 The ceramic granule powder has an absorption peak intensity of 0.023 counts or more having a peak top at

2. 2. The granular powder of claim 1, wherein the ceramic is zirconia.

3. The granular powder according to claim 2, wherein the zirconia is a stabilizing element-containing zirconia.

4. 4. The granular powder according to claim 3, wherein the stabilizing element is one or more selected from the group consisting of yttrium, magnesium, calcium, cerium and erbium.

5. 3. The granular powder according to claim 1, wherein the binder is at least one of a polyvinylpyrrolidone-based resin and an acrylic-based resin.

6. The granular powder according to claim 1 or 2, wherein the content of the binder is 0.1% by mass or more and 8% by mass or less.

7. Lightly packed bulk density is 1.10 g / cm 3 The granular powder according to claim 1 or 2.

8. The granular powder (15±0.5 g) was filled into a cylindrical mold having a diameter of 25 mm and press-molded at a pressure of 49 MPa. The measured density was 2.70 g / cm 3 The granular powder according to claim 1 or 2.

9. 2. The method for producing granular powder according to claim 1, further comprising a step of spray-drying a slurry containing ceramic powder, a binder and a solvent at a temperature difference between hot air and exhaust air of 55° C. or more.

10. The method according to claim 9, wherein the hot air temperature is 300° C. or less.

11. A method for producing a molded product, using the granular powder according to claim 1 or 2.

12. A method for producing a calcined body, which uses the molded body according to claim 11.

13. A method for producing a sintered body, which uses the molded body according to claim 11 or the calcined body according to claim 12.

Citation Information

Patent Citations

  • Ceramic granules, method for producing ceramic granules, and ceramic molded body

    WO2013047413A1

  • Zirconia composition, partially sintered material and sintered material and methods for production thereof, and laminate

    WO2018056331A1